Biocompatibility of Dead Sea Water and retinyl palmitate carrying poly(3-hydroxybutyrate-co-3-hydroxyvalerate) micro/nanoparticles designed for transdermal skin therapy. (September 2015) - Eke, Gozde; Goñi-de-Cerio, Felipe; Suarez-Merino, Blanca; Hasirci, Nesrin; Hasirci, Vasif
In this study, novel drug carriers were developed for the treatment of skin conditions such as psoriasis, aging, or ultraviolet damage using micro/nanocapsules and micro/nanospheres of poly(3-hydroxybutyrate-co-3-hydroxyvalerate). The sizes of the particles were in the micron range and were loaded with retinyl palmitate and Dead Sea Water. In some tests, MgCl2 was used as a substitute for Dead Sea Water for accurate determination of released ions of Dead Sea Water. Encapsulation efficiency and loading of water-soluble excipients Dead Sea Water and MgCl2 were almost eight times lower than the hydrophobic compound retinyl palmitate. The particles were not cytotoxic as determined with the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide test using L929 mouse fibroblasts, BALB/3T3 mouse embryo fibroblasts, and HaCaT human keratinocytes. Ames test showed that the carriers were not genotoxic. The particles penetrated the membrane of human osteosarcoma cells Saos 2 and accumulated in their cytoplasm. No reactive oxygen species production could be detected which indicated low or no inflammatory response toward the particles. In the tests with intact human skin, 1.2% of the retinyl palmitate–loaded poly(3-hydroxybutyrate-co-3-hydroxyvalerate) particles penetrated into the human skin, but when the skin was without stratum corneum and increased to 6.9%. In conclusion, these carriers have shown a significant potential as topical drug delivery systems in the personalized treatment of skin diseases because their contents could be modified according to a patient's needs and several drugs could be loaded in one type of microparticle, or several populations, each carrying a different drug, can be used in the treatment.